Efektivitas Pemanfaatan GeoGebra Dengan Tipe STAD Terhadap Pemahaman Konsep Matematis Siswa Pada Materi Matriks di Kelas XI SMA Negeri 14 Medan T.A 2025/2026 - Pangaribuan, Gustin Magdalena; Sihombing, Dame Ifa; Naibaho, Tutiarny (Universitas PGRI Semarang, 2026)
This study aims to examine the effectiveness of using GeoGebra based on the Student Teams Achievement Divisions (STAD) model in improving students’ understanding of mathematical concepts in the matrix curriculum for XI-grade students at State SMA Negeri 14 Medan T.A 2025/2026. The method used was quantitative research with a quasi-experimental design. The study population consisted of 11th-grade students, with a sample of 69 students from classes XI 4 and XI 5 selected through purposive sampling. The instruments used included an essay test, a questionnaire, and an observation sheet. The research results indicate that all five indicators of effectiveness were met: (1) the instructional structure was in the “good” category, based on evaluations by two out of three observers, who assigned scores of 86 and 87, respectively; (2) teacher communication was good, with two observers assigning a score of 34; (3) student response was good, as evidenced by 57 out of 69 students falling within the “good” frequency range; (4) student activity was good, with 62 students in the good category according to three observers; (5) learning achievement was complete without remedial instruction, with 58 students (91.3%) scoring in the 66–85% range. Thus, the use of the STAD method with GeoGebra is effective in enhancing students’ understanding of mathematical concepts.